Sistem Pengambilan Nomor Antrian Berbasis Website Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bulukumba - Fatimah Azzahra; Husni sulaiman; Andi Nurul Faizah (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to: (1) To design a website-based queue number retrieval system for the population and civil registration service in Bulukumba Regency. (2) To implement a queue number retrieval system at the Bulukumba Regency population and civil registration service. Because the development of information technology has had a major influence on organizational or agency activities, especially on the existing queuing system, while the queuing system at the Population and Civil Registration Office of Bulukumba Regency is still manual so that people have to come directly to the office to take queue numbers, so this is less efficient for taking numbers queue. Based on the existing problems, the queuing system is a solution where this queuing system is easier to access without having to wait long to get a queue number. This study uses the Waterfall method. This Waterfall model consists of several stages, namely analysis, design, coding, testing, implementation and maintenance. Based on the results of the tests that have been carried out in this study, a website-based queue number retrieval system was designed and built based on the problems that occur in taking queue numbers at Dukcapil, in designing this queuing system using UML as the system design and built using the php programming language using MySql database as database storage and using the waterfall method in the system development stage, testing is carried out using the black box method and based on the tests carried out this system is in accordance with the design. The results of the implementation of a website-based queue number retrieval system at the Bulukumba Regency population and civil registration service, namely assisting the community in taking queue numbers and assisting staff in preparing reports.